A golden age : a novel - Anam, Tahmima, 1975- (Dhaka : Shahitya Prakash ; New York : HarperCollins, 2007)
As she plans a party for her son and daughter, Rehana Haque's life will be transformed in a story of one family caught in the middle of the 1971 Bangladesh War of Independence, as they face changes and decisions that will have a profound impact on their lives.
AAL
New Age International
Keywords: Widows -- Bangladesh -- Fiction; Family -- Bangladesh -- Fiction; Bangladesh -- History -- Revolution, 1971 -- Fiction; Domestic fiction; Historical fiction